1981
DOI: 10.1099/00222615-14-1-41
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of staphylococci to fatty acids: novel inactivation of linolenic acid by serum

Abstract: SUMMARY.The inhibition of coagulase-negative staphylococci and Staphylococcus aureus of human or animal origin by most free fatty acids was similar, but coagulase-positive staphylococci were sensitive and coagulase-negative cultures were resistant to linolenic acid. Animal strains of S. aureus were more sensitive to linolenic acid than were human strains. These differences were reflected in the relative abilities of the three categories of strains to survive on human skin.The antibacterial effects of 20 mg of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 15 publications
0
30
1
Order By: Relevance
“…aureus. 12 Strains from the SCBU, where survival on hands was presumably important, were not more resistant than those from elsewhere, or than controls, by the methods we used. Others have also found only a narrow range of sensitivity of staphylococci to skin fatty acids.…”
Section: Discussionmentioning
confidence: 83%
“…aureus. 12 Strains from the SCBU, where survival on hands was presumably important, were not more resistant than those from elsewhere, or than controls, by the methods we used. Others have also found only a narrow range of sensitivity of staphylococci to skin fatty acids.…”
Section: Discussionmentioning
confidence: 83%
“…The carotenoid protects S. aureus from oxidative stress by scavenging radicals (42). Staphyloxanthin may also provide resistance to other stresses like desiccation and light exposure (43,44). Previous field and laboratory studies on photoinactivation of Enterococcus spp.…”
mentioning
confidence: 99%
“…Pathogens that failed to show inhibition by either category of FA included Pseudomonas aeruginosa and Escherichia coli (Zheng et al 2005) and Listeria monocytogenes (Reiner et al 1986). (Gutteridge et al 1974;Butcher et al 1976;Altenbern 1977b;Kondo and Kanai 1977;Heczko et al 1979;Lacey and Lord 1981;Knapp and Melly 1986;Rohrer et al 1986;Hogan et al 1988;Thompson et al 1990;Ababouch et al 1992;Wang and Johnson 1992;Thompson et al 1994;Petrone et al 1998;Sun et al 2003) C18:3 Kabara et al 1972;Raychowdhury et al 1985;Reiner et al 1986;Mbandi et al 2004;Zheng et al 2005)** Note: When the lipid number fails to distinguish between similar FA, common names of fatty acids are given in parentheses.…”
Section: Comparison 4 Polyunsaturated Versusmentioning
confidence: 97%
“…In pooled data from 20 of 22 studies, most comparisons showed greater pathogen inhibition by omega-3 FA than by omega-6 FA (Figure 4c). Two studies, excluded from Figure 4c because they did not provide the exact identification of pathogen strains, also showed stronger bacterial inhibition by omega-3 FA (Heczko et al 1979;Lacey and Lord 1981). Heczko et al showed that of 242 strains of Staphylococcus aureus, most strains were sensitive to the omega-3 linolenic acid (C18:3) at a minimum concentration of 0.19 mmol/L while most strains were inhibited by the omega-6 linoleic acid at a minimum concentration of 6.25 mmol/L (Heczko et al 1979).…”
Section: Comparison 2 Short-and Medium-chain Saturated Fatty Acids Vmentioning
confidence: 97%
See 1 more Smart Citation